The Path from the Hustler to the Man Who Does Sex Work: Changes and Perspectives in Anglophonic Literature (Global Journal of Human-Social Science, 2025)
This article explores the academic literature on male sex work, particularly on Englishlanguage publications. This research covers more than 150 articles and books, offering a literature review that investigates three distinct historical periods: the hustler as a social problem; the male sex worker as a vector of disease; and sex work as a profession. Our analysis reveals the development of perceptions about male sex work, highlighting its transition from a pathologizing understanding to a more professionalized recognition. Issues of identity, economics, Health, and technology are examined, demonstrating how the intersection of these factors shapes men's experiences and lives within the sex industry. Case studies from diverse geographies illustrate the varied academic concerns, from violence and legislation to Public Health and sex tourism. This article highlights the predominance of Health in this field of study, reflecting on the implications of this concern for the dissemination and impact of knowledge about male sex work.
Keywords: sex work; men; english language; Health